Differences Of Menstrual Cycle Before and After Hemodialysis In Women Suffering Chronic Kidneys - Siti Nurjanah, Fitriani Nur Damayanti, Alfina Aprilia Riafisari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The menstrual cycle is part of the regular process that prepares a woman's body each month for pregnancy. The bleeding period, known as the menstrual period (or menses, or menstruation), (Saryono, 2009). Factors that can cause menstrual pattern disorders are systemic disorders such as chronic renal failure. Chronic Kidney Disease in the world is currently experiencing an increase and becoming a serious health problem, the results of the 2010 Global Burden of Disease study, Chronic Kidney Disease was the 27th leading cause of death in the world in 1990 and increased to 18th place in 2010. This type of research is an observational analytic study using a cross sectional approach. This research was conducted in August-October 2020. The author took the place of research in the Hemodialysis Room (HD) Roemani Muhammadiyah Hospital Semarang. The results of the study based on the Paired Sample Test output table showed that the Sig. (2-tailed) is 0.001 <0.05, then H0 is rejected and Ha is accepted. So it can be denied that there is a difference in the average between the menstrual cycle before and after hemodialysis. Chronic kidney failure itself causes hormonehormonal disruption. From the results of the study, it was found that there was a menstrual cycle before and after undergoing hemodialysis in women with CRF at Roemani Muhammadiyah Semarang Hospital